Exploring knowledge, attitudes and perceived myths towards foetal programming and factors affecting it among the public and health professionals in Pakistan: a needs assessment study - Syeda Sadia Fatima; Zakaria, Maheen; Zakaria, Aliza; Tekian, Ara (Journal of the Pakistan Medical Association, 2023)
Objective: To explore knowledge, attitudes and practices of laypersons and health professionals towards foetal programming, and factors affecting it. Method: The mixed methods study was conducted at the Aga Khan University, Karachi, from January 20 2021 to May 13, 2022, and comprised adults of either gender with access to social media platforms. Data was collected using an online survey questionnaire in English and Urdu developed to capture responses from a diverse pool of participants. The survey tool was circulated through WhatsApp, Facebook and Instagram. Two focus group discussions were conducted; one with laypersons in group A and the other with health and allied professionals in group B. Data was analysed using SPSS 21, while data related to focus group discussions was subjected to thematic analysis. Results: Of the 358 participants, 173(48.3%) were in group A and 185(51.7%) were in group B. There were 34(18.4) subjects in group A and 27(15.6) in group B who had knowledge of foetal programming (p>0.05). Only factors related to father’s health and dietary elements on the foetus were significantly different between the groups (p<0.05). Thematic analysis led to the formation of 3 overarching themes: parent’s lifestyle, comorbidity and diet on foetal health; myths and cultural beliefs regarding foetal development; and the need for training / awareness for practitioners and community. Conclusion: Lack of knowledge and misinformation about foetal programming and development was common among health professionals and laypersons. Key Words: Foetal programming, Obesity, Nutrition, Midwives, Nursing, Public health.